Identifikasi Jenis Serangga Hama pada Tanaman Padi (Oryza Sativa L.) di Kampung Surau Kabupaten Dharmasraya - Anugrah, Chici; Zulyusri, Zulyusri (Asian Journal of Science, Technology, Engineering, and Art, 2024)
The aim of the research is to identify insect pests on rice plants (Oriza sativa) in Kampung Surau, Dharmasraya Regency. The method used is direct capture, direct identification by looking at body morphology and using Google Lens. The results of the research show that insect pests in the rice fields are low because they only consist of 7 species of insect pests on rice plants (Oryza sativa), namely black ants (Dolichoderus thoracicus), stalked crabs (Anasa tristis), grasshoppers (Dissoitera carolina), rice caterpillar larvae ( Pyraloidea innota), leaf beetles (Cryptocephalus Beetles), white pests (Nhympula depunctalis) and fierce grasshoppers (Letocorisa acuta).